2017
DOI: 10.1088/1361-6595/aa56d6
|View full text |Cite
|
Sign up to set email alerts
|

Power coupling mode transitions induced by tailored voltage waveforms in capacitive oxygen discharges

Abstract: Low-pressure capacitively coupled radio frequency discharges operated in O 2 and driven by tailored voltage waveforms are investigated experimentally and by means of kinetic simulations. Pulse-type (peaks/valleys) and sawtooth-type voltage waveforms that consist of up to four consecutive harmonics of the fundamental frequency are used to study the amplitude asymmetry effect as well as the slope asymmetry effect at different fundamental frequencies (5, 10, and 15 MHz) and at different pressures (50-700 mTorr). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(103 citation statements)
references
References 53 publications
7
96
0
Order By: Relevance
“…To simplify the analysis, secondary electron emission is omitted in the model, only the reflection of the impinging electrons is taken into account with a probability of 20% [51]. The gas temperature is fixed at T g = 350 K. For the surface quenching probability of O 2 (a 1 ∆) singlet delta molecules we use the value of α = 6 · 10 −3 [25,39,48]. The computations are carried out using a spatial grid with N x = 100−1600 points and N t = 2000−85000 time steps within the RF period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the analysis, secondary electron emission is omitted in the model, only the reflection of the impinging electrons is taken into account with a probability of 20% [51]. The gas temperature is fixed at T g = 350 K. For the surface quenching probability of O 2 (a 1 ∆) singlet delta molecules we use the value of α = 6 · 10 −3 [25,39,48]. The computations are carried out using a spatial grid with N x = 100−1600 points and N t = 2000−85000 time steps within the RF period.…”
Section: Methodsmentioning
confidence: 99%
“…[24]. Derzsi et al investigated electron power absorption mode transitions in oxygen discharges driven by tailored voltage waveforms [25]. They concluded that changing the number of consecutive harmonics included in the driving voltage waveform has a strong effect on the electronegativity of the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original study many investigations have demonstrated this effect through both simulation and experiment and extended it to the use of more than two frequencies to increase the amplitude asymmetry of the waveform [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. It has also been demonstrated that an electrical asymmetry can be generated using sawtooth-like waveforms where the rise and fall times of the voltage waveform differ [41][42][43][44][45][46][47][48]. In this case, the dc self-bias is generated as a result of a so-called slope asymmetry as opposed to the previously discussed amplitude asymmetry.…”
Section: Introductionmentioning
confidence: 97%
“…For example, it has been shown that the dc self-bias formed in electrically asymmetric plasmas can change over a wide range dependent on the gas in which the plasma is formed [44] and can thus be difficult to predict. The electronegativity of the plasma, which in part determines the electron heating mode [52], has been found to be particularly important in this regard [31,37,44,48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation